KARAKTERISTIK PERUBAHAN ORGANISASI SEBAGAI UPAYA PENINGKATAN KINERJA PERUSAHAAN DI INDUSTRI BATIK MASARAN SRAGEN JAWA TENGAH - Lukman Hakim; Eko Sugiyanto (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
The objectives of this study are: (1) To identify the causes oforganizational changes that occur in the Sragen Masaran Batikindustry. (2) Identifying the impact of organizational change in theSragen Masaran Batik industry. (3) Analyzing the stages oforganizational change that occur in the Sragen Masaran Batikindustry. This study uses a descriptive method with a case studyapproach (Case Studies). Case studies are in-depth studies ofindividuals, one group, one organization, one program of activities,and so on within a certain time.The results of the study concludedthat the causes of organizational change: (1) adjustment factors tothe environment, (2) technological development, (3) governmentencouragement to improve the effectiveness of the industry, (4)changes in regulations or new systems in organizations, (5) changesin consumer tastes, (6) demands for organizational and employmentchanges. The impact of changes include: (1) changes in workprocedures, quality and quantity of labor, (2) changes in decisionmaking techniques at the leadership, (3) internal conditions in aconducive organization, (4) development goals and industrialstrategies become more focus, (5) occurrence of work evaluation orimprovement of industrial activities. Stages of change include: (1)conducting an assessment, (2) conducting an identification, (3)setting changes, (4) determining the strategy, (5) conducting anevaluation.